The Complexities of Counting Fish: Engaging Citizen Scientists in Fish Monitoring - Bieluch, Karen; Willis, Theodore; Smith, Jason; Wilson, Karen (Maine Policy Review, 2017)
Data gathered by citizen scientists can help ecologists understand long-term trends and can improve the quality and quantity of data about a resource. In Maine and Massachusetts, numerous citizen science programs collect data on river herring, anadromous fish that migrate each spring from the ocean to spawn in rivers and lakes. In collaboration with state and local resource managers and academic institutions, these programs aim to protect and restore river herring, improve local watersheds, and in some cases, support commercial harvesting. To better understand how programs are run and how data are used by managers, we interviewed program coordinators and resource managers. Interviews revealed that resource managers consider citizen science–generated river herring data in decision making, but that their concerns about data quality affect if and how data are used. Although not without challenges, standardizing monitoring approaches could improve data collection and use. We offer six considerations related to standardization for managers.